Notaries' Escrow Services in Selling Real Estate in the Republic of Slovenia - Bojan Podgoršek (LeXonomica, 2020)
Notary's escrow is a legal relationship between the notary and the parties to the underlying legal transaction, which is generally a sales agreement. Notary’s escrow is regulated with mandatory statutory rules commissioning public notaries and the rules of the mandate agreement. Mutual obligations of the parties to the underlying legal transaction in and of themselves do not influence the notary's obligations under a notary's escrow agreement unless they are included in the notary's escrow agreement as a constituent part thereof. Slovenian legislation stipulates the general conditions of notaries' operations. However, it does not stipulate specific conditions that must be fulfilled in order to place documents, funds and securities into escrow with a notary, nor does it stipulate the mandatory component elements of the escrow order. Therefore, The Slovenian regulation of notary's escrow should be supplemented.